PERAN PEREMPUAN SUKU ARFAK DALAM PENDIDIKAN ANAK STUDI KASUS DI DISTRIK WARMARE KABUPATEN MANOKWARI PROVINSI PAPUA BARAT - DJULIATI DAMPA; AGTHA WAHYU WIDIATI (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2009)
This research aims to recognize the role of Arfak women as housewife in their children's education (academic and non academic), also to analyze the factor that influence the role of housewife in children education.